Pilot-scale Trials of Plantation on Representative Mine Degraded Land - a Case Study from Goa - Sharma, Jitendra Vir; Choudri, B. S.; Sridharan, P. V. (Indian Forester, 2007)
Impact of mining upon land, air and water has been debated for quite some time. The present intense mining activity at the expense of the environment has resulted in global awareness to undertake studies to provide means of countering environmental damage. In Goa, indiscriminate mining has resulted in profound ecological degradation. Mines and their dumps are situated on hillocks. As a result during heavy monsoon, huge quantities of silt material from dumps washes away and deposits in the nearby agricultural fields, water courses and private and public lands located at low levels and contributes towards degradation of these resources. Pilot scale trials of plantation on representative degraded land were conceived and planned experiments carried out. These advanced techniques of rehabilitation would help in controlling further degradation of resources. Techniques have been developed looking at the existing dump material in Goa and three models of rehabilitation carried out. These have been found to give results in the improvement of physico-chemical properties of the soil, reduction in soil erosion, improvement in water conservation and green coverage of the area. The details of these models of rehabilitation and their application in the context of Goa are discussed in this paper.